2021
DOI: 10.1016/j.ijid.2020.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory pathogen diversity and co-infections in rural Zambia

Abstract: Objectives: The role of respiratory co-infections in modulating disease severity remains understudied in southern Africa, particularly in rural areas. This study was performed to characterize the spectrum of respiratory pathogens in rural southern Zambia and the prognostic impact of co-infections. Methods: Respiratory specimens collected from inpatient and outpatient participants in a viral surveillance program in 2018–2019 were tested for selected viruses and a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…In our study, the majority of patients (71%) with coronavirus were under 18 years old. There were 45% of (18). It can be seen that coronavirus infection occurs frequently at younger age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, the majority of patients (71%) with coronavirus were under 18 years old. There were 45% of (18). It can be seen that coronavirus infection occurs frequently at younger age.…”
Section: Discussionmentioning
confidence: 96%
“…Another study of respiratory pathogen diversity and coinfections in rural Zambia (18) showed that respiratory viral co-infection was less in adults than in children, but it was not related to the difference with clinical severity.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the wide variety of LRTI viruses and their difficulty to detect, viral examinations were often performed for epidemiological purposes. However, the awareness that viral infections cause hospital infections and early diagnosis of viral agents will decrease use of antibiotics has shown that diagnosis of respiratory tract infection viruses is very important (3).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of the above coronaviruses in co-infection did not consistently associate with worse outcome, type of illness, or age groups with some exceptions [2,29]. Few studies validated co-infections with secondary confirmatory diagnostics which raises concern for specificity [2,30].…”
Section: Lessons From Comparative Human Coronavirology and Co-infectionmentioning
confidence: 97%